Optimisation of medications used in residential aged care facilities: a systematic review and meta-analysis of randomised controlled trials - Almutairi, Hend; Stafford, Andrew; Etherton-Beer, Christopher; Flicker, Leon (2020)
Background: Frail older adults living in residential aged care facilities (RACFs) usually experience comorbidities and are frequently prescribed multiple medications. This increases the potential risk of inappropriate prescribing and its negative consequences. Thus, optimising prescribed medications in RACFs is a challenge for healthcare providers.